Species diversity, dominance and management of Shorea lumutensis-stand at Pangkor Island, Perak, Malaysia - Hamzah, Mohd. Zaki; Salleh@Japri, Mohd Nazre; Abdul Malek, Ismail Adnan; Alias, Mohamad Azani; Zainal Abidin, Latifah; Suterisno, Siti Eryani; Suryanto, Priyono (Universiti Putra Malaysia Press, 2013)
High Conservation Value Forest (HCVF) stand of Shorea lumutensis, one of the endemic dipterocarps in Peninsular Malaysia, was established in Pangkor Island, Perak, Malaysia to conserve the species. The study was carried out at the HCVF stand to identify species dominance and social behaviour of S. lumutensis for future ex-situ rehabilitation effort. A total of six (6) sample plots (in the size of 50 x 50m each) were prepared. The richness, heterogeneity and evenness analyses by the principle component analysis were carried out on five canopy layers such as emergent or super tree (ST), dominant (T1), co-dominant and suppressed (T2), shrub (S) and herb (H). The H-layer showed higher richness for Plot 1 (P1), P2 and P3, with 69.141, 65.178 and 83.135, respectively, and a high level of heterogeneity. Meanwhile, the ST-layer recorded the lowest values for richness, evenness and heterogeneity. No single species dominates the S, T2 and T1 layers. The S layer in P3 and P5 is dominated by Diospyros subrhomboidea and Aporosa frutescens, respectively, while Fordia unifoliata, Vatica pauciflora, Teijsmanniodendron coriaceum are dominant in P6. On the other hand, the T1 layer (Plot 3) is dominated by Shorea maxwelliana, Vatica pauciflora and Hopea latifolia. Only two individuals of S. lumutensis are found in the T1- ST layers of all plots, showing the lesser dominance of the species. Hence, it is suggested that bigger HCVF area is needed to protect the species.